2004
DOI: 10.1007/s00705-004-0317-8
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of Tomato yellow leaf curl virus (TYLCV) and other plant viruses with a GroEL homologue from the whitefly Bemisia tabaci

Abstract: To avoid destruction in the haemolymph of their vector, many plant circulative viruses interact with GroEL homologues produced by insect endosymbiotic bacteria. We have exploited this phenomenon to devise tools allowing trapping of plant viruses by either GroEL purified from the whitefly Bemisia tabaci or by whitefly GroEL over-expressed in E. coli. PCR tubes or 96-well plates coated with a GroEL preparation were incubated with cleared sap of virus infected plant leaves or insect vectors. GroEL-bound viruses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…This predicts that the "Ca. Tremblaya princeps" GroEL homolog is able to bind GLRaV-3 coat protein whereas E. coli GroEL cannot, the latter observation having been confirmed (1). The data suggest a role for "Ca.…”
Section: Microscopic Localization Of Endosymbiontsmentioning
confidence: 67%
See 1 more Smart Citation
“…This predicts that the "Ca. Tremblaya princeps" GroEL homolog is able to bind GLRaV-3 coat protein whereas E. coli GroEL cannot, the latter observation having been confirmed (1). The data suggest a role for "Ca.…”
Section: Microscopic Localization Of Endosymbiontsmentioning
confidence: 67%
“…Others (1,30,31,41) have found that (for other insect-transmitted viruses in sucking insects) a specific region of the intact virus (i.e., the assembled viral coat) binds to the endosymbiont GroEL and that mutant viruses do not persist in the insect. For the virus to be specifically transported from the gut to the salivary glands without being degraded there must be some protein specifically binding to the virus.…”
Section: Discussionmentioning
confidence: 99%
“…play a role in transmission (69). In whiteflies, prior feeding with anti-GroEL antibodies strongly reduced TYLCV transmission (58), and binding of geminivirus CP to GroEL confirmed the specificity of this interaction (3,57). However, since the CP of NT isolates of AbMV still bound to GroEL (57), its role in transmission appears controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, it was revealed that, these GroEL expressed in the plant phloem trapped the TYLCV particles. Further, it was demonstrated that whitefly derived-GroEL expressing tomato plants have provided moderate resistance to TYLCV [2,3].…”
Section: Involvement Of Bacterial Proteins In Providing Tolerance Agamentioning
confidence: 99%
“…Moreover, due to equal affinity of the antiviral Endosymbiotic bacterial GroEL proteins TYLCV particles will be trapped by GroEL in the plant phloem TYLCV Tomato [2,3] Recombinant antibodies Antibody fragments corresponding to the target viral proteins hinder the necessary viral infection.…”
Section: Involvement Of Bacterial Proteins In Providing Tolerance Agamentioning
confidence: 99%